2020
DOI: 10.1002/pd.5768
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term outcomes of gestational diabetes and its treatment on fetal development

Abstract: Globally the prevalence of gestational diabetes mellitus (GDM) is rising mainly due to the increase in maternal obesity. A number of different methods to screen for and diagnose GDM have been described although consensus on the preferred methods does not yet exist. GDM has significant short‐ and long‐term health risks for the mother, developing fetus and the children born to mothers with GDM. Short‐term risks for the fetus include macrosomia (excessive birthweight), shoulder dystocia, birth trauma, and hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 50 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…Finally, fetal programming in GDM has been studied in the context of DOHaD hypothesis (developmental origins of health and disease) to understand the long-term consequences of growing in a hyperglycemic environment during life in utero. Hyperglycemia and maternal obesity generate epigenetic changes in fetal programming, increasing the risk for obesity, T2DM, impaired glucose tolerance, insulin resistance, coronary heart disease, chronic arterial hypertension, dyslipidemia, metabolic syndrome, and some cancers in the future life of the newborn [ 3 , 323 , 324 , 325 , 326 , 327 ]. Interestingly, it has been observed that GDM effects in childhood are manifested after two years of age, such as an increase in BMI and hyperglycemia [ 328 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, fetal programming in GDM has been studied in the context of DOHaD hypothesis (developmental origins of health and disease) to understand the long-term consequences of growing in a hyperglycemic environment during life in utero. Hyperglycemia and maternal obesity generate epigenetic changes in fetal programming, increasing the risk for obesity, T2DM, impaired glucose tolerance, insulin resistance, coronary heart disease, chronic arterial hypertension, dyslipidemia, metabolic syndrome, and some cancers in the future life of the newborn [ 3 , 323 , 324 , 325 , 326 , 327 ]. Interestingly, it has been observed that GDM effects in childhood are manifested after two years of age, such as an increase in BMI and hyperglycemia [ 328 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
“…Since then, diverse research papers have scrutinized these cellular cascades, and finally, in 1995, the role of PI3K and Akt in the glycemic control and other metabolic activities of insulin was described [39,40]. After IR-B binding to insulin, PI3K binds to tyrosinephosphorylated IRS proteins, leading to the formation of phosphatidylinositol (3,4,5)triphosphate (PIP3). Downstream effects of PIP3 lead to activation of 3-phosphoinositide dependent protein kinase (PDK)1 and the subsequent activation of a variety of kinases, of which Akt 1-3 is the best-studied [41].…”
Section: The Insulin and Igf-i/igf-ii Axis And Molecular Pathways Primarily Disturbed In Gdm Placentaementioning
confidence: 99%
See 1 more Smart Citation
“…Fetal hyperinsulinemia, and macrosomia may result from inadequate blood glucose management in pregnant women with GDM ( 15 ). GDM has long-term negative impacts on children, including an increased incidence of Type 2 diabetes and obesity ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The global increase in maternal obesity has also driven a rise in gestational diabetes mellitus. Murray and Reynolds review the consequences of gestational diabetes mellitus (GDM) and examine emerging concerns with use of the oral glucose‐lowering drugs, metformin, and glibenclamide 4 . Maternal preexisting diabetes can have much more profound effects on fetal development than GDM.…”
mentioning
confidence: 99%